Soil organic carbon storage in different agroforestry systems associated with coffee in Nariño, Colombia - Delgado-Vargas, Ivan A.; Benavides Franco, Natalia (Agronomía Mesoamericana, 2024)
Introduction. Anthropogenic activities are one of the causes of the increase in global temperature, which affects agro-environmental, ecological and socioeconomic processes. The contributions of agricultural production systems in the capture and storage of greenhouse gases have been little studied. Still, the literature indicates that the inclusion of trees on farms is an option to capture and store some greenhouse gases. Objective. To evaluate the relationship between floristic and structural diversity of coffee production systems and soil organic carbon (SOC) storage. Materials and methods. The study was carried out during the period 2019-2020, in three localities Sandoná, San Pablo and Buesaco, Nariño-Colombia. Twelve agroecosystems with coffee were visited, where Shannon-Weiner and Simpson indices, tree density and complete soil analysis with samples at 30 cm depth were evaluated. An analysis of variance and principal components was sufficient for the analysis of the information. Results. The SOC was not presented statistical differences (p > 0.05), which ranged between 38.55 Mg ha-1 in the full sun coffee arrangement in Buesaco and 96.63 Mg ha-1 in the coffee arrangement with miscellaneous in the same municipality, which presented the highest species diversity. Conclusions. It was proved that the coffee harvest associated with agroforestal systems (T3 and T4) with higher diversity and abundance of species, is higher than carbon accumulated in the soil compared to the monoculture arrangement (80,43 Mg ha-1 vs 58,32 Mg ha-1, severally), this diversification give to the family and environment some services and goods, contributing to the mitigation of climate change.